Visualization of Learning Analytics on E-Learning Information System Subject - elisa riani; rika yuniartini; Andharini Dwi Cahyanic (Universitas Trunojoyo Madura, 2017)
E-Learning as the concept of education today that utilize computer network technology to do the learning, but the E-learning at less value in assesing the behaviour pattern of students to learn because E-learning has not been able to provide an appropriate learning features with the character of students doing learning. In order to learning process on the E-learning system attractive and easily evaluated by lecturer or students, it is necessary to visual learning analytics in the system. Visual learning analytics conducted to analyze with the last result in the form of learning-based images, graphs, or diagrams. The system uses E-learning Information systems courses, the system processed by take the log of E-learning as a source to behaviour pattern of user, and then data are group based on determined criteria. The results of these grouping then visualized in form of a speedometer. By implemented this system, lecturer can easily observed, evaluated and asses the behaviour of students in do the learning, and students can evaluated behaviour patterns himself in do the learning. Based on the trial results were applied, overall the systems can be implemented properly by the students and lecturer with an average value of 7.7 out of students and the average value of 8 from lecturers is entered into either good category.